Self-Regulation of Learning in Practice Behavior: Exploratory Observation Study of Indonesian Young Badminton Players - Listiyani Siegit; Hugh Richard (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
Self-regulated learning is an essential skill in maintaining deliberate practice over years, espe-cially for young athletes. Yet, there has not been many studies done on athlete’s practice behavior. This study measured the behavioral correlation of self-regulation of learning in Indonesian young badminton players during practice. There were two parts of this study: first, a list of behavioral items was generated from coach interviews with six expert badminton coaches. Second, the list was used to observe players practice behavior during three separate practices and the observed players were asked to complete a self-regulation of learning questionnaire. Eleven badminton players aged 12 to 19 from different divisions participated voluntarily in this study. The observation and questionnaire results showed good self-regulation of learning in badminton players. However, the components breakdown did not match with coaches’ concept of self-regulated learning. Players were scored high in effort, yet lacking in metacognitive components which led to less proactive behavior in their learning process. This study highlighted the importance of gaining a complete impression of the players’ self-regulated learning skills during practice to develop and maximise their potential.